2017
DOI: 10.1039/c6dt04265a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and reactivity of tantalum corrole complexes

Abstract: Reaction of the free base corrole (Mes(p-OMePh)corrole)H with tantalum trialkyl precursors TaMeCl and TaBnNBu resulted in the formation of the tantalum dichloride (1) and tantalum imido (4) corrole complexes via alkane elimination. The X-ray crystal structures of these two compounds have been determined and the structural parameters are discussed. The Ta centre of 1 was found to sit out of the plane of the corrole ring by 0.903 Å and is cis-ligated, similarly to what has been reported for group 4 porphyrin com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…The characteristic appearance of this molecule with two ligands protruding from the convex side of a bowl‐shaped entity is reminiscent of the visual perception of a Viking helmet and tempted us to address these types of activated metal porphyrinoids as “Viking helmet corroles”. Similar structures are known from several early transition metal porphyrins and phthalocyanines, and the molecular structures of tantalum and tungsten corroles with the same Viking helmet type coordination have recently been reported ,…”
Section: Methodssupporting
confidence: 75%
See 1 more Smart Citation
“…The characteristic appearance of this molecule with two ligands protruding from the convex side of a bowl‐shaped entity is reminiscent of the visual perception of a Viking helmet and tempted us to address these types of activated metal porphyrinoids as “Viking helmet corroles”. Similar structures are known from several early transition metal porphyrins and phthalocyanines, and the molecular structures of tantalum and tungsten corroles with the same Viking helmet type coordination have recently been reported ,…”
Section: Methodssupporting
confidence: 75%
“…In situ ligand‐exchange studies monitored by X‐band EPR spectroscopy revealed the replacement of the chlorine atoms by methyl, (trimethylsilyl)methyl, vinyl, and phenyl groups (see the Supporting Information), opening up the organometallic realm for molybdenum corroles. Particularly instructive is the reaction with sodium cyclopentadienide (NaCp) with 4 and 5 , which results in the formation of air‐ and moisture‐stable diamagnetic half‐sandwich complexes, the molybdenum(IV) corrolocenes 7 and 8 , . 8 readily crystallized from a dichloromethane solution upon diffusion of n ‐pentane.…”
Section: Methodsmentioning
confidence: 99%
“…Alkyne-stabilized masked Ta III hydrides can stoichiometrically insert isonitriles and alkynes into the Ta-H bond, followed by C-C reductive coupling of the bound alkyne to give butadienyl and azadiene fragments 151 . Dimethyltantalum corrole complexes can react with CO to give coupled diacetyl complexes 152 . This process is presumed to occur via insertion of two CO molecules into the two Ta-Me bonds, followed by reductive elimination of the two acyl ligands to give diacetyl, which then binds to the resulting low-valent tantalum as the ene-diolate form to formally oxidize Ta III to Ta V .…”
Section: Reductive Coupling Reactionsmentioning
confidence: 99%
“…Among these, 4d and 5d metals, lanthanides, and actinides are known to be incorporated in the corrole cavity to afford the corresponding complexes. A very recent addition to the “periodic table of corrole complexes” is a Ta V corrole . Complexation of corroles with main‐group elements such as B III , P V , and Ge IV has already been accomplished.…”
Section: Introductionmentioning
confidence: 99%